Éco-conception dans le secteur des TIC et relocalisation des activités : étude de cas dans des TPE françaises - Gilles Puel; Valérie Fautrero (Développement Durable et Territoires)
This paper presents the first results of an empirical research on the emerging practices of eco-design in the field of information technology (IT) in french VSB. Motivations of entrepreneurs favor social and environmental pillar at the expense of the economy. This social dimension is coupled with a territorial dimension "local": sustainability of the model implemented is based on a rational consumption and the restructuring of production chains to anchor the activities in the territories, closer to consumers. However, these efforts come up against economic reality and the lack of market.